FETOMATERNAL OUTCOME OF GESTATIONAL DIABETES MELLITUS IN PRIMIGRAVIDA DELIVERED AT TERTIARY CARE HOSPITAL - Vishnoi, Nirmla; Jakhar, Rekha; Choudhary, Ankita; Bharia, Monika (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: To determine the Prevalence of gestational diabetes mellitus (GDM) in primigravida and their feto-maternal outcome who delivered at tertiary care hospital in western Rajasthan. Methods: A retrospective chart review study will be conducted on primigravida delivered at the department of Obstetrics and Gynaecology, MDM Hospital Dr. S. N. Medical College, Jodhpur, Rajasthan, India from May 2022 to December 2022. Results: The prevalence of GDM in primigravida was 6.42%, maximum occurrence between 34 and 36 weeks of gestation (53.3%). 8.8% of GDM patients had a preterm delivery, out of these 8 women polyhydramnios were seen in 4 women. 49% had lower segment cesarean section and 3% had instrument delivery. preeclampsia was seen in 25.56%, urinary tract infection in 10%, preterm labor was seen in 8.89%, premature rupture of membrane was seen in 5.56% of the study population. 10% of babies were low birth weight. The incidence of congenital anomalies was seen in 6.6%. Intrauterine death was seen in 2 babies who had congenital anomalies. Conclusion: GDM is associated with adverse complications in both the mother and fetus.